2009
DOI: 10.1167/iovs.08-1810
|View full text |Cite
|
Sign up to set email alerts
|

Low-Spatial-Frequency Channels and the Spatial Frequency-Doubling Illusion

Abstract: The results support earlier reports, that there are several low-spatial-frequency channels below 1 cyc/deg in the periphery. The results may have implications for the FDT and matrix perimeters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…These produce the FD percept across the field. 16 A Bayesian threshold estimation strategy is applied to provide thresholds with normal attenuation values numerically comparable to those attained using standard forms of static perimetry. 17 VF loss is typically seen at an earlier clinical stage with Matrix than with more traditional automated static perimetry that utilize focal light stimuli flashed for 0.2 seconds in an illuminated bowl (as used in our prior study).…”
Section: Methodsmentioning
confidence: 99%
“…These produce the FD percept across the field. 16 A Bayesian threshold estimation strategy is applied to provide thresholds with normal attenuation values numerically comparable to those attained using standard forms of static perimetry. 17 VF loss is typically seen at an earlier clinical stage with Matrix than with more traditional automated static perimetry that utilize focal light stimuli flashed for 0.2 seconds in an illuminated bowl (as used in our prior study).…”
Section: Methodsmentioning
confidence: 99%
“…3 The gratings modulated at the temporal and spatial frequencies described here exhibit the FD illusion for VF locations like those used here. 22 Importantly, the selected frequencies in the stimulus band mean that any frequencies generated by second order interactions between regions are separate from the second harmonic and noise frequencies. 2,3 Testing Conditions Stimuli were presented at three different viewing distances, 16, 32, and 128 cm (Figs.…”
Section: Stimulus Frequencies and Data Acquisitionmentioning
confidence: 99%
“…2,3,8 The postulated link between illusory frequency doubling and magnocellular Y-cells has also been questioned by Zeppieri and colleagues 9 based on the finding that the perceived frequency is not always double that of the stimulus grating but can attain a range of fractional frequencies. Also, Rosli et al 10 using factor analysis found that three factors were able to account for 79.3% of the variance in the probability in seeing frequency doubling in highcontrast gratings. This does not seem to indicate that the percept of frequency doubling is linked uniquely to the magnocellular system.…”
Section: B C Skottun and J R Skoylesmentioning
confidence: 99%